Recovering Together: The Socioecological Impact of Social Networks on Postpartum Substance Use Disorder Recovery. - Holcomb, Leah A.; Koob, Caitlin; Treado, Bonnie; Mayo, Rachel; Cartmell, Kathleen B.; Barkin, Jennifer; Dickes, Lori; Eichelberger, Kacey (Community Mental Health Journal, 2025)
This study explored the experiences of postpartum individuals in early substance use disorder (SUD) recovery and key aspects of their social networks using the Socioecological Model (SEM). We conducted a qualitative study of 22 postpartum individuals (< 1 year since delivery) in residential SUD treatment from July to November 2023. Transcribed, audio-recorded interviews were analyzed using Atlas.ti, with findings organized by SEM levels. Participants, primarily White (81.8%), single (86.3%), and living below the poverty line (81.8%), reported opioid (40.1%) and stimulant (81.8%) use disorders. Challenges spanned SEM levels, including navigating parenthood, accessing trauma-informed care, and overcoming structural barriers such as housing instability, transportation, and childcare access. Findings underscore the need for family-centered, trauma-informed recovery programs and flexible policies addressing childcare and social service barriers to support long-term recovery and maternal well-being.